2012
DOI: 10.1051/0004-6361/201219473
|View full text |Cite
|
Sign up to set email alerts
|

Constant cross section of loops in the solar corona

Abstract: Context. The corona of the Sun is dominated by emission from loop-like structures. When observed in X-ray or extreme ultraviolet emission, these million K hot coronal loops show a more or less constant cross section. Aims. In this study we show how the interplay of heating, radiative cooling, and heat conduction in an expanding magnetic structure can explain the observed constant cross section. Methods. We employ a three-dimensional magnetohydrodynamics (3D MHD) model of the corona. The heating of the coronal … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
88
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 68 publications
(105 citation statements)
references
References 46 publications
17
88
0
Order By: Relevance
“…Loops in the model match observations in terms of diameter, or cross section [68,102]. In general, loop structures found in observations, such as thin or thick loops at constant cross section, or expanding envelopes of several thin loops, are also seen in the three-dimensional MHD models [103].…”
Section: (A) Synthetic Observationssupporting
confidence: 56%
See 2 more Smart Citations
“…Loops in the model match observations in terms of diameter, or cross section [68,102]. In general, loop structures found in observations, such as thin or thick loops at constant cross section, or expanding envelopes of several thin loops, are also seen in the three-dimensional MHD models [103].…”
Section: (A) Synthetic Observationssupporting
confidence: 56%
“…The loop in a particular EUV band reflects only a small range in temperature, so that a very high temperature at the top of an expanding magnetic tube will effectively cut off the top part and thus lead to a loop that looks like it has a constant cross section [102]. This scenario is also found with loops in a more dynamic situation of a model of an emerging active region [68].…”
Section: (B) Structure Of Coronal Loopsmentioning
confidence: 72%
See 1 more Smart Citation
“…Using TRACE 171 Å observations, already Zhang et al (1999) had found that the width of the emission associated to fibrils was nearly the same at different heights: at their photospheric root as well as ≈30 Mm higher up in the atmosphere. It was speculated as a possible explanation that, either the observed emission might not be sensitive to the detection of the desired canopy structure-as recently supported by Peter and Bingert (2012), see Sect. 1.4.2 for details-or that network fields in the QS could, by some mechanism, be prevented from fanning out (Zhang 2005).…”
Section: Doubts About the Concept Of A Magnetic Canopymentioning
confidence: 79%
“…Peter and Bingert (2012) used an MHD model to investigate the temporal evolution of the corresponding synthesized coronal emission. They were able to show how emission of seemingly constant width may arise from an expanding flux tube.…”
Section: Coronal Loopsmentioning
confidence: 99%